Linking supply chain management practices to customer relationship management objectives: a proposed framework - Saad, Nourhan Ahmed; Elgazzar, Sara; Mlaker Kac, Sonja (Business: Theory and Practice, 2022)
This research proposes a framework linking supply chain management (SCM) practices to customer relationship management (CRM) objectives through better organizational performance. First, critical review was conducted to identify the relationship between SCM practices and organizational performance. Then, a systematic review of published research work on CRM objectives for last two decades was conducted with the purpose of identifying key variables for CRM objectives and their impact on SCM practices through managing organizational performance. The review revealed a set of main variables for CRM objectives (customer satisfaction and customer loyalty). Upon which, a theoretical framework has been developed linking SCM practices to CRM objectives through enhancing organizational performance. This work brings together the concepts of SCM practices and organizational performance. It also provides a comprehensive review on CRM objectives over a time span (2000–2019) in order to develop the framework between SCM practices and CRM objectives through better organizational performance. The proposed framework can help practitioners to understand SCM practices that can lead to better CRM and hence better organizational performance.